Advances in medical research on wildlife from illegal trade and accidents in Boyacá, Colombia (2023)
Colombia has environmental conditions that favor the diversity of biological organisms and allow it to be considered a megadiverse country. Boyacá, a department of the country, has within its geographical and environmental characteristics altitudes ranging from 145 to 3,100 m above sea, which generates a scenario of thermal floors and ecosystems that facilitate the natural location of species of diverse fauna and flora. In addition, it has been recognized as one of the ten departments with the highest fauna extraction at national level. In another vein, illicit trafficking is the fourth illegal activity that moves the most money in the world (between 7,000 and 23,000 million US/year), with an alarming increase in the post-pandemic period. From this perspective, rescued, confiscated, or voluntarily surrendered fauna must be attended to standardized medical-surgical protocols and clinical ranges that are as specific as possible. In the temporary home of the Juan de Castellanos University Foundation, in agreement with Corpoboyaca, advances research processes are carried out both in the microbiology of mucous membranes, skin and appendages, as well as in resistance to antibiotics, cardiovascular physiology, biomarkers, imaging, behavioral pathology and animal welfare, on different taxa of the received wildlife, which are kept under professional care for a while in the transit home, to later be relocated or released according to their specific condition.